Atención plena disposicional y estilos de manejo de conflictos en adolescentes de secundaria - Luna Bernal, Alejandro César Antonio (2021)
The present study aimed to analyze the relationship between dispositional mindfulness and three styles of interpersonal conflict management (aggressive, passive and cooperative) in adolescent middle-school students. A study was carried out with a quantitative approach, of a non-experimental type, with a cross-sectional design and correlational scope. The participants were 120 students from a public school in Guadalajara, Jalisco, Mexico, aged 12 to 15 years.  They answered the Conflictalk Questionnaire and the Freiburg Mindfulness Inventory-short version. The findings showed a statistically significant positive correlation between cooperative style and dispositional mindfulness. These findings are discussed within the frame of the current interest of education in constructive conflict resolution skills of adolescents in the school context.